Michele Piccirillo (1944-2008) francescano di Terra Santa e archeologo - Bottini, Giovanni Claudio (Liber Annuus, 2008)
Abstract Father Michele Piccirillo, a Franciscan friar of the Custody of the Holy Land (1944-2008) was a Professor and Archaeologist of the Studium Biblicum Franciscanum from 1974 until his death. This essay gives a short account of his life, the most part of which he spent in Jerusalem. It recalls his activity as a lecturer, his studies and research of an historical and archaeological character, carried out during a period of over thirty years in various fields: Crusader history and art, archaeological research especially in Jordan and Syria, the archaeological museum of the Flagellation, the history of the Custody of the Holy Land and Franciscan Palestinology. There is also a delicate indication as to the spiritual attitude with which this Franciscan priest faced his illness and death. From the vast bibliography a chronological list of books, contributions (that have appeared in scientific magazines and cultural periodicals), is given.